TABUNGAN SAFARI DI KOSPIN JASA SYARIAH BATANG : PERSPEKTIF HUKUM EKONOMI SYARIAH - Frika Arista; Rita Rahmawati (el hisbah: Journal of Islamic Economic Law, 2022)
Kospin Jasa Syariah is one of the Service Cooperative institutions that has many products, one of which is the Safari Savings product. Safari Savings is a term savings with profit sharing in the form of free tours. The contract used in this Safari Savings is a mudharabah contract, where Kospin Jasa Syariah is the mudharib and the customer is the shaahibul maal. However, in practice at the Batang Syariah Services Kospin, it turns out that it is not in accordance with the DSN-MUI Fatwa Number 86/DSN-MUI/XII/2012 concerning Prizes in Funding for Islamic Financial Institutions because in the safari savings there is a prize in the form of money. The purpose of this study was to determine the practice of Safari Savings at Kospin Jasa Syariah Batang and to find out the perspective of Sharia Economic Law regarding the giving of gifts in the form of money. This type of research is a field research (field research) with a qualitative approach. The data sources consist of primary data obtained by observation and interview techniques to the management of Kospin Jasa Syariah Batang and 5 customers selected by accidental sampling technique. Secondary data in the form of literature books, research journals, theses, research results, and documents relevant to the research obtained with documentation techniques. Data were analyzed by descriptive analysis technique. Based on the results of the study, it can be concluded that in terms of the practice of drawing prizes in the form of money in Safari Savings it is not in accordance with the Fatwa of DSN MUI, there are several points that are not in accordance with the Fatwa of DSN MUI No. 086/DSN-MUI/XII/2012 concerning Prizes in Funding for Islamic Financial Institutions. Keywords: Safari Savings, MUI DSN Fatwa, Prize Draw